2018
DOI: 10.15761/tit.1000252
|View full text |Cite
|
Sign up to set email alerts
|

Management of heart transplant recipients with hemodynamically significant clinical rejection in the presence of antibodies against angiotensin II type 1 receptor: A retrospective study

Abstract: Antibodies against Angiotensin II Type 1 Receptor (AT1R-Abs) have been associated with allograft rejection in heart transplantation. Data is lacking for modalities to mitigate their effect on cardiac function. We describe a case series consisting of patients with clinical and/or biopsy indication of rejection with detectable AT1R-Ab and present treatment regimen and outcome. Clinical dysfunction was defined as hemodynamically significant cardiac dysfunction on echocardiogram including a decrease in ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Additionally, kidney transplant patients with vascular rejection remained rejection free and had fewer AT1R antibodies after treatment involving PP, 100 mg of losartan daily plus IVIG, 107 or 4 mg of candesartan daily plus 6 sessions PP, 3 d of 1 g/d methylprednisolone, and 6 doses of 1.5 mg/kg/d ATG. 108 Furthermore, in a case series, 109 it was reported that 9 of the 12 (75%) heart transplant recipients had AT1R antibodies, and 6 out of these 9 developed AMR or mild rejection. Seven patients were treated with 25–100 mg losartan and/or PP and IVIG, and 71% (5 of 7) recovered good graft function.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Additionally, kidney transplant patients with vascular rejection remained rejection free and had fewer AT1R antibodies after treatment involving PP, 100 mg of losartan daily plus IVIG, 107 or 4 mg of candesartan daily plus 6 sessions PP, 3 d of 1 g/d methylprednisolone, and 6 doses of 1.5 mg/kg/d ATG. 108 Furthermore, in a case series, 109 it was reported that 9 of the 12 (75%) heart transplant recipients had AT1R antibodies, and 6 out of these 9 developed AMR or mild rejection. Seven patients were treated with 25–100 mg losartan and/or PP and IVIG, and 71% (5 of 7) recovered good graft function.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…These antibodies can bind to the vascular endothelium and induce apoptosis independent of CDC. Representative examples include MHC I chain-related gene A (MICA) [47,48], angiotensin II type I receptor (AT1R) [49,50 ▪▪ ], endothelin-1 type A receptor (ETAR) [51], endothelial cell antigens [52], vimentin [53], K-α-1-tubulin [54], collagen-V [55], anticardiac myosin antibody [56], and other non-HLA IgM antibodies. In cardiac transplantation, anti-MICA and antiendothelial antibodies have been associated with increased AMR [57] and the development of CAV [47,56].…”
Section: Nonhuman Leukocyte Antigen Antibodiesmentioning
confidence: 99%